Current Progress of Nanomaterials in Molecularly Imprinted Electrochemical Sensing. (2nd January 2018) - Zhong, Chunju; Yang, Bin; Jiang, Xinxin; Li, Jianping
ABSTRACT: Nanomaterials have received much attention during the past decade because of their excellent optical, electronic, and catalytic properties. Nanomaterials possess high chemical reactivity, also high surface energy. Thus, provide a stable immobilization platform for biomolecules, while preserving their reactivity. Due to the conductive and catalytic properties, nanomaterials can also enhance the sensitivity of molecularly imprinted electrochemical sensors by amplifying the electrode surface, increasing the electron transfer, and catalyzing the electrochemical reactions. Molecularly imprinted polymers that contain specific molecular recognition sites can be designed for a particular target analyte. Incorporating nanomaterials into molecularly imprinted polymers is important because nanomaterials can improve the response signal, increase the sensitivity, and decrease the detection limit of the sensors. This study describes the classification of nanomaterials in molecularly imprinted polymers, their analytical properties, and their applications in the electrochemical sensors. The progress of the research on nanomaterials in molecularly imprinted polymers and the application of nanomaterials in molecularly imprinted polymers is also reviewed.